Penghitungan Pajak Penghasilan Pasal 21 Atas Kenaikan Gaji - Widjaja, Siana M. (Pelita Harapan University, 2006)
Application guidelines of deduction, payment and reporting of Income Tax article 21 and article 26 contained in Regulation of Director General of Taxation No 15/PJ/2006 dated February 23. 2006 only give examples of computation of the income tax article 21 upon salary increase retroactiveapplied from the beginning of the year. Â Computation examples of the income tax article 21 and article 26 upon salary increase retroactive applied from the middle of the year and salary increase in the middle of the year without retroactive adjustment are not given. So, this article try to explain the computation examples of the income tax article 21 upon those salary increases.